The dilemma of gas importing and exporting countries - Ieda Gomes (The Oxford Institute for Energy Studies, 2020)
At a time of low prices and an apparent surplus of supply in the global gas market it is important to try and identify new sources of demand, especially for LNG. In this respect, one interesting theme is how some countries are switching from their traditional role as LNG exporters to becoming importers of gas as their indigenous demand grows. Ieda Gomes explores this concept using the case studies of Malaysia and Indonesia, and she attempts to identify the key drivers behind the shifts in the gas economies of both countries. Significantly, though, there are also a few countries where gas has an existing role in the domestic energy economy, and which have historically imported gas, which have now found new gas resources and are starting to export. A prime example of this is Argentina, where the discovery of large shale gas resources has led to a gas surplus and the opportunity to generate export revenues. This paper analyses this example as a contrast to the first two and examines whether it is a sustainable situation. Overall, we believe that this paper can provide some important insights into the factors which can influence the position of gas in a country's energy balance, especially if the prevalence of hydrocarbons has created a dependency via subsidies prices or other politically-driven strategies. There are a number of other examples around the world where the demands of the domestic market can undermine a country's ability to export its energy resources, and as a result we hope that this analysis can provide a greater understanding of the key drivers and consequences of this outcome.
Keywords: 330; Argentina; Exports; Gas; Imports; Indonesia; LNG; Malaysia; NG 161